2015
DOI: 10.2500/ajra.2015.29.4149
|View full text |Cite
|
Sign up to set email alerts
|

The Blood-Brain Barrier and Nasal Drug Delivery to the Central Nervous System

Abstract: Despite extensive efforts to develop new techniques to cross the BBB, none has proved sufficiently effective in reaching the brain, whereas minimizing adverse effects and the endoscopic mucosal grafting technique offers new potential promise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 67 publications
(107 reference statements)
0
45
0
Order By: Relevance
“…In humans and nonhuman primates, drug delivered into the nasal cavity is primarily deposited in the respiratory zone located between the inferior and middle turbinate, and is absorbed into the systemic circulation (Pires et al, 2009;Grassin-Delyle et al, 2012). Some lines of research have suggested that IN drug administration may permit direct absorption to the brain that circumvents the blood-brain barrier (Dhuria et al, 2010;Johnson et al, 2010;Miyake and Bleier, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In humans and nonhuman primates, drug delivered into the nasal cavity is primarily deposited in the respiratory zone located between the inferior and middle turbinate, and is absorbed into the systemic circulation (Pires et al, 2009;Grassin-Delyle et al, 2012). Some lines of research have suggested that IN drug administration may permit direct absorption to the brain that circumvents the blood-brain barrier (Dhuria et al, 2010;Johnson et al, 2010;Miyake and Bleier, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…4,318,319 The intranasal route plays a role in overcoming the BBB and targeting the drugs directly to the brain. 282,[319][320][321][322][323][324][325] However, the oral, dermal, and intravenous routes can be used to administration of nanodevices …”
Section: Remarks and Challengesmentioning
confidence: 99%
“…In their review, Miyake and Bleier discuss the challenges of formulating drug targeting strategies to bypass the blood-brain barrier and deliver therapeutics to the central nervous system (CNS). 12 The authors describe the innovative use of endoscopic grafting techniques to facilitate drug administration to the subarachnoid space via an intranasal route. 12 A nasal mucosal surgical flap is created employing established skull base reconstruction methods to serve as a vehicle for pharmaceutical delivery to the CNS.…”
mentioning
confidence: 99%
“…12 The authors describe the innovative use of endoscopic grafting techniques to facilitate drug administration to the subarachnoid space via an intranasal route. 12 A nasal mucosal surgical flap is created employing established skull base reconstruction methods to serve as a vehicle for pharmaceutical delivery to the CNS. 12 As more advanced endoscopic skull base procedures are developed, it is important to assess the clinical outcomes of such surgeries.…”
mentioning
confidence: 99%
See 1 more Smart Citation